Neomerinthe ornithoptera, a new species of scorpionfish (Teleostei: Scorpaenidae) from the southwestern Pacific Ocean, with a reassessment of the diagnosis for N. pallidimacula (Fowler 1938) - Matsumoto, Tatsuya; Motomura, Hiroyuki (Zootaxa, 2024)
Neomerinthe ornithoptera n. sp., described on the basis of three specimens from Fiji and the Wallis and Futuna Islands, southwestern Pacific Ocean, was previously reported as Neomerinthe pallidimacula (Fowler 1938), due to its characteristic lack of both lateral lacrimal and second preopercular spines. The new species is clearly distinguished from Indo-Pacific congeners, including N. pallidimacula, by the following combination of characters: pectoral-fin rays 18; scale rows in longitudinal series 44 or 45; pored lateral-line scales 23; scale rows above lateral line 6 or 7, below lateral line 12, between sixth dorsal-fin spine base and lateral line 5, between last dorsal-fin spine base and lateral line 5; upper gill rakers 6, lower gill rakers 13, total gill rakers 19; longitudinal ridge on lateral surface of maxilla absent; many small cycloid scales on base of pectoral fin and ventral surface of body between isthmus and posterior to pelvic fin; pectoral-fin ray length 37.6–40.0% of SL; first anal-fin spine length 6.9–8.5% of SL; second anal-fin spine length 23.3–25.5% of SL; third anal-fin spine length 22.7–23.1% of SL; pelvic-fin spine length 17.9–18.1% of SL; longest pelvic-fin soft ray length 26.6–29.2% of SL; and several lower pectoral-fin rays markedly elongated. In addition, the diagnosis of N. pallidimacula shows the species to be similar to Neomerinthe bucephalus (Alcock 1896), although distinguished from the latter by the following features: upper-jaw length 25.0% of SL; maxilla depth 8.2% of SL; eleventh dorsal-fin spine length 5.7% of SL; and 22 pored lateral-line scales.